2019
DOI: 10.1093/annonc/mdz127
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase III KEYNOTE-045 trial of pembrolizumab versus paclitaxel, docetaxel, or vinflunine in recurrent advanced urothelial cancer: results of >2 years of follow-up

Abstract: Background Novel second-line treatments are needed for patients with advanced urothelial cancer (UC). Interim analysis of the phase III KEYNOTE-045 study showed a superior overall survival (OS) benefit of pembrolizumab, a programmed death 1 inhibitor, versus chemotherapy in patients with advanced UC that progressed on platinum-based chemotherapy. Here we report the long-term safety and efficacy outcomes of KEYNOTE-045. Patients and methods Adult patients with histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
330
3
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(347 citation statements)
references
References 16 publications
10
330
3
4
Order By: Relevance
“…135 Long-term results (.2 years' follow-up) from this same phase III trial were consistent with earlier reports, with longer 1-and 2-year OS and PFS results for pembrolizumab compared with chemotherapy. 136 The median DOR was not reached for pembrolizumab compared with 4.4 months for chemotherapy. Pembrolizumab also showed lower rates of any grade (62% vs 90.6%) and grade $3 AEs (16.5% vs 50.2%) compared with chemotherapy.…”
Section: Pembrolizumabmentioning
confidence: 98%
“…135 Long-term results (.2 years' follow-up) from this same phase III trial were consistent with earlier reports, with longer 1-and 2-year OS and PFS results for pembrolizumab compared with chemotherapy. 136 The median DOR was not reached for pembrolizumab compared with 4.4 months for chemotherapy. Pembrolizumab also showed lower rates of any grade (62% vs 90.6%) and grade $3 AEs (16.5% vs 50.2%) compared with chemotherapy.…”
Section: Pembrolizumabmentioning
confidence: 98%
“…1C-E). In contrast, bladder cancers have a reported higher clinical response rate to ICB (27) and interestingly, the staining of bladder cancer TMAs show low PD-L2 expression, but predominant PD-L1 ligand expression in bladder cancer cells (n=208) ( Fig. 1D and 1E).…”
Section: Pd-l2 Is Abundantly Expressed In Human Ovarian Cancers But Nmentioning
confidence: 95%
“…Most of the patients included in these trials had urothelial carcinomas of bladder. Only Pembrolizumab 93,94 and Atezolizumab 95 have Phase III randomized data published (KEYNOTE 045 and IMVigor 211, respectively). Other checkpoint inhibitors have been evaluated with Phase II single-arm trials ( Table 3) with favorable objective response rates and toxicities profile.…”
Section: Peri-operative Systemic Therapy -Immunotherapymentioning
confidence: 99%
“…[96][97][98][99] Within KEYNOTE 045 and IMVigor 211, it is important to note that up to 27% of the included trial population were diagnosed with UTUCs; however, no further published data exist for this sub-group yet. [93][94][95] As these immunotherapeutic agents are increasingly utilized, it is important to be familiar with associated toxicities associated. A systematic review and meta-analysis of treatment-related adverse events of PD-1 and PD-L1 inhibitors used in 125 clinical trials involving 20,128 patients 100 found that the most common all-grade adverse events were fatigue (18.26%; 95% CI, 16.49-20.11%), pruritus (10.61%; 95% CI, 9.46-11.83%), and diarrhea (9.47%; 95% CI, 8.43-10.58%), while the most common grade 3 or higher adverse events were fatigue (0.89%; 95% CI, 0.69-1.14%), anemia (0.78%; 95% CI, 0.59-1.02%), and aspartate aminotransferase increase (0.75%; 95% CI, 0.56-0.99%)…”
Section: Peri-operative Systemic Therapy -Immunotherapymentioning
confidence: 99%